Exploring Social Media as an Alternative Learning Source to Boost History Learning Interest Among Grade X Students of SMAN 5 Palu: An Instagram and YouTube Case Study - Raudhatul Jannah; Minarni Nongtji; Hasan; Juraid (Journal of Education and Teaching Learning, 2026)
Exploration of the Role of Social Media as an Alternative Learning Resource in Increasing Interest in History Learning among Tenth-Grade Students of SMAN 5 Palu: A Case Study of Instagram and YouTube. Undergraduate Thesis. History Education Study Program, Department of Social Science Education, Faculty of Teacher Training and Education, Tadulako University. First Advisor: Dr. Minarni Nongtji, S.Pd., M.Si., Second Advisor: Dr. Hasan, M.Hum. This research aims to explore the role of Instagram and YouTube social media as alternative learning resources in increasing interest in learning history among tenth-grade students of SMA Negeri 5 Palu. This study employs a descriptive qualitative method with a case study approach. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis was conducted through the stages of data condensation, data display, and conclusion drawing and verification. The results of this study indicate that Instagram and YouTube social media serve as alternative learning resources capable of increasing the learning interest of tenth-grade students at SMAN 5 Palu. Both platforms make learning more engaging, varied, and encourage students' active participation and independent learning. Although there are obstacles regarding networks, data packages, and learning focus, the use of social media remains effective if properly directed and supervised within the learning process.